Dampak Covid-19 terhadap Perubahan Psikologis, Sosial dan Ekonomi Pasien Covid-19 di Kelurahan Dendang, Langkat, Sumatera Utara - Aslamiyah, Suaibatul; Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The Corona Virus Disease 2019 (COVID-19) has caused unrest for all levels of society. The virus, whose symptoms are similar to SARS, not only affects a person's physical condition, but also affects psychological, social, and economic conditions. Among the general population, people infected with this virus or COVID-19 patients are more likely to experience changes in psychological, social, and economic conditions. This study aims to describe the impact of COVID-19 on psychological, social, and economic changes in patients in Dendang village Langkat regency, North Sumatera. The method used in this research is descriptive qualitative with interview techniques to patients who have undergone treatment and recovered. The results showed that there were changes in the psychological, social, and economic aspects of COVID-19 patients. Psychologically, patients experience changes ranging from fear, sadness, depression, decreased motivation to trauma. While the social impact, patients get different treatment and views from society. Then, economically, patients experience a decrease in income so that it is difficult to meet their food needs.